Silk Fibroin Periodic Surface With Low Mid-Infrared Reflectivity Fabricated via Laser-Induced Forward Transfer - Couto, Filipe A.; Paula, Kelly T.; Santos, Moliria V.; Ribeiro, Sidney J.L. [UNESP]; Mendonça, Cleber R. (Optica Publishing Group, 2023)
2D periodic surfaces of silk-fibroin microstructures were fabricated via femtosecond Laser-Induced Forward Transfer, presenting low reflectivity at the mid-infrared region. Also, the low reflectivity feature was further enhanced by coating the structures with carbon.